At the Origins of Chartism: James O’Brien - Darya A. Avakyan; Kirill M. Anderson; Olga D. Talskaya (RUDN Journal of Political Science)
The issues related to the causes of the formation of Chartist ideology in England in the XIX century, as well as the influence of this movement on the subsequent development of European socio-political thought are to examine. The assessments of the Chartist movement in Russian and foreign historiography are analyzed separately. Special attention is paid to the life path and creative legacy of James O’Brien (1805-1864), one of the brightest Chartist leaders, publicist, journalist and reformer, whose activities and radical position of a militant Irishman set the tone for the entire working-class movement in England. Another undeniable merit of O’Brien is his quite successful attempt at a theoretical and ideological justification of the Chartist movement, which none of his contemporaries tried to undertake. The authors dwell in the most detail on the content of his fundamental work O’Brien “The Rise, Progress and phases of human slavery: how it came into the world and what needs to be done to make it go away.” It is in this work that one can find not only vivid calls for struggle, but also trace the connection of his ideas not only with the parliamentary history of Britain, but also with the general history of the labor movement.